Appraisal of the Impacts of Women in Musical Culture of the Yoruba of South-West Nigeria - Oluwadamilare, Julius Oluwayomi (Journal of Gender and Power, 2023)
Musically, world over, women have played outstanding roles in musical practices in various cultures of the world. Women have played the role of educator at one time or the other while teaching their children traditional social values through folktales, folk songs, proverbs, poetry, praise songs, praise names, religious and secular songs. Oral history and oral traditions in every culture in Africa have stories about the achievement of women in such cultures. Ever since pre-historic times, lessons on morals, history and practical knowledge, have been passed from one generation to another, through oral tradition. In this way, the accumulated experiences of the older generation that have been gathered at one time or the other were passed to the younger ones through oral tradition. This paper therefore appraises the impacts of Women in Musical Culture of the Yoruba of South-West Nigeria. The findings of the study revealed that women are custodians, promoters and transmitters of cultural values in the society through song, dance and folktales; women are good organizers, managers and promoters of musical performances; women do use music to educate people and correct some erring members of the society and also, that women play active role in the advancement of music scholarship and patronage in Nigerian society. It is therefore recommended that more of indigenous/traditional songs be encouraged in in our society in the present day Nigeria where civilization tends to have rendered such songs ineffective.